2018
DOI: 10.1016/j.parkreldis.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Poor nighttime sleep is positively associated with dyskinesia in Parkinson's disease patients

Abstract: Background Dyskinesia is a troublesome complication of long-term dopaminergic medications in Par-kinson’s disease (PD) patients. Many factors are reported to be associated with dyskinesia in PD. Objective To investigate the association between sleep quality and dyskinesia in patients with PD. Methods Four hundred twenty-five patients with PD were enrolled in this study. Demographic information was collected. Unified Parkinson’s Disease Rating Scale (UPDRS) and Hoehn and Yahr (H-Y) stage scale were also per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…Our 1‐week actigraphy data demonstrated a clear negative correlation between eTST and the severity of dyskinesia. Poor nighttime sleep has been positively associated with LID in a recent study with a large cohort of patients . Along these lines, sleep deprivation has been shown to enhance LID in a rodent model and in PD patients .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our 1‐week actigraphy data demonstrated a clear negative correlation between eTST and the severity of dyskinesia. Poor nighttime sleep has been positively associated with LID in a recent study with a large cohort of patients . Along these lines, sleep deprivation has been shown to enhance LID in a rodent model and in PD patients .…”
Section: Discussionmentioning
confidence: 93%
“…DYS patients start from a lower early SWA level compared to the ADV and DNV subjects. However, the observed SWA reduction in early sleep could be a consequence of a chronic deficit of synaptic downscaling during the night in dyskinetic patients . In these respects, chronic sleep deprivation has been associated with an impairment of synaptic potentiation …”
Section: Discussionmentioning
confidence: 98%
“…In addition, sleep disturbances may contribute to the progression of symptoms. Studies have shown that worsening of sleep quality and shortening of sleep duration are markers of the prodromal phase of PD and an increased number of sleep-related symptoms and poor night-time sleep are positively correlated with disease-related disability [ 6 , 26 ]. A recent study showed that sleep fragmentation recorded by actigraphy was associated with an increased burden of PD pathology in the brain [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are generally refractory to, or exacerbated, by standard anti-parkinsonian medications. In this context, it should be mentioned that impaired synaptic downscaling associated with sleep disruption may promote the emergence of motor complications caused by standard pharmacological therapy (Galati et al, 2015), and that this idea is supported by clinical studies indicating a correlation between disrupted sleep and l-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia (Mao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%